Confidentiality and Consent Issues in Psychotherapy Case Reports: The Wolf Man, Gloria and Jeremy - Thomas-Anttila, K (John Wiley & Sons, 2015)
In this article I explore the issues surrounding confidentiality and consent in the writing of psychotherapy case reports. An important theme is the challenge of protecting a patient's privacy while furthering knowledge in the field through publication. I discuss some of the complexities as well as the relevance of present day requirements for informed consent, including a consideration of the provisions within the Declaration of Helsinki (1964, last revised 2013). To illustrate the difficulties inherent in writing about our work I give examples of three cases: Freud's patient Sergei Pankejeff (the ‘Wolf Man’), Gloria (the patient in the ‘Gloria Films’), and a contemporary patient, ‘Jeremy’, whose therapist published an account of her work with him. The writing of case material is complex and resists easy solutions; there can be no ‘one-size-fits-all’ approach but instead the therapist writer's careful consideration on a case by case basis of his or her motivations for writing, what the patient is really consenting to, whether patient consent can ever be truly informed, and how writing and publishing a case might impact on the safety and well-being of the patient (including others connected to the patient), as well as on the therapeutic relationship itself.
Keywords: Writing case reports; Confidentiality; Informed consent; ethics; Analyst–patient relationship; Psychoanalytic psychotherapy